2010
DOI: 10.1111/j.1865-1682.2010.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Bos taurus Steers with Babesia bovis Recombinant Antigens MSA-1, MSA-2c and 12D3

Abstract: The purpose of this research was to evaluate the recombinant proteins MSA-1, MSA-2c and 12D3 as a combined immunogen for cattle. Fifteen steers were randomly assigned into three groups of five animals each (I, II and III). On day 0, cattle in group I were injected with 50 microg each of rMSA-1, rMSA-2c and r12D3 with the adjuvant Montanide 75; cattle in Group II received adjuvant-PBS, and Group III were untreated controls. On day 14, cattle in Group I received a second injection of the three recombinant protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…bovis based on recombinant antigens [3, 11, 12, 22]. The merozoite surface antigens (MSAs) were considered to be good vaccine candidate, as the antisera raised against the recombinant forms of these antigens blocked the erythrocyte invasion of B .…”
mentioning
confidence: 99%
“…bovis based on recombinant antigens [3, 11, 12, 22]. The merozoite surface antigens (MSAs) were considered to be good vaccine candidate, as the antisera raised against the recombinant forms of these antigens blocked the erythrocyte invasion of B .…”
mentioning
confidence: 99%
“…[ 7 , 30 ]. These tests are not useful for diagnosing bovine babesiosis during the clinical phase of the disease but are used for epidemiological studies or to evaluate antibabesial antibody titers after cattle vaccination [ 4 , 7 , 24 , 30 , 31 ]. The IFAT provides adequate sensitivity and is easy to perform [ 12 ]; however, it has some disadvantages in the analysis of samples, such as the low number that can be performed per day, depending on the operator’s ability and expertise, and the results are influenced by the subjective judgment of the analyst [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Babesia bovis recombinant merozoite surface antigen 1 (rMSA-1) was expressed and prepared as previously described [ 24 ]. Briefly, transformed E. coli TOP10 cells containing the recombinant pBAD/ThioTOPO®, (ThermoFisher Scientific, Waltham, MA, USA) plasmid inserted with the msa-1 gene were resuspended in lysis solution containing sarcosyl (0.03%) and protease inhibitors DNase and RNase and incubated for 3 h at room temperature with gentle agitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that these recombinant proteins generate high antibody titers in immunized cattle that are capable of inhibiting parasite invasion in vitro . However, in vivo trials demonstrated lack of protection against parasite challenge with field isolates ( 40 , 41 ). Moreover, cattle immunized with a multi-epitope modified vaccinia Ankara virus and recombinant proteins were not protective after challenging by a virulent B. bovis strain ( 41 ).…”
Section: Control Of Bovine Babesiosis With the Use Of Immunogensmentioning
confidence: 99%